Cost effectiveness of drug eluting coronary artery stenting in a UK setting: cost–utility study. Issue 1 (14th April 2005) - Bagust, A; Grayson, A D; Palmer, N D; Perry, R A; Walley, T
Abstract : Objective: To assess the cost effectiveness of drug eluting stents (DES) compared with conventional stents for treatment of symptomatic coronary artery disease in the UK. Design: Cost–utility analysis of audit based patient subgroups by means of a simple economic model. Setting: Tertiary care. Participants: 12 month audit data for 2884 patients receiving percutaneous coronary intervention with stenting at the Cardiothoracic Centre Liverpool between January 2000 and December 2002. Main outcome measures: Risk of repeat revascularisation within 12 months of index procedure and reduction in risk from use of DES. Economic modelling was used to estimate the cost–utility ratio and threshold price premium. Results: Four factors were identified for patients undergoing elective surgery (n = 1951) and two for non-elective surgery (n = 933) to predict risk of repeat revascularisation within 12 months. Most patients fell within the subgroup with lowest risk (57% of the elective surgery group with 5.6% risk and 91% of the non-elective surgery group with 9.9% risk). Modelled cost–utility ratios were acceptable for only one group of high risk patients undergoing non-elective surgery (only one patient in audit data). Restricting the number of DES for each patient improved results marginally: 4% of stents could then be drug eluting on economic grounds. The threshold price premium justifying 90% substitution of conventional stents was estimated to be £112 (US212, €162) (sirolimus stents) or £89 (US167, €130) (paclitaxel stents). Conclusions: At current UK prices, DES are not cost effective compared with conventional stents except for a small minority of patients. Although the technology is clearly effective, general substitution is not justified unless the price premium falls substantially.